Effect of single operator cholangioscopy on accuracy of bile duct cytology. Issue 12 (8th August 2020) - Aly, Fatima Zahra; Mostofizadeh, Sayedamin; Jawaid, Salmaan; Knapik, Jacquelyn; Mukhtar, Faisal; Klein, Robert
Abstract: Introduction: This is the first study to evaluate the accuracy of bile duct brushings since the introduction of single operator cholangioscopy SpyGlass DS system in 2015. The primary aim of our study was to compare the accuracy of cytology brushings against biopsies obtained at endoscopic retrograde cholangiopancreatography (ERCP) and cholangioscopy. Method: A retrospective search for bile duct brushing specimens was performed and the charts reviewed. The gold standard for definitive diagnosis of malignancy was surgical tissue or compelling clinical evidence of malignancy. Definite negative diagnosis relied on lack of clinical/imaging features of malignancy on follow‐up. Results: There was no significant difference in diagnostic accuracy of cytology specimens obtained at different procedures. Overall sensitivity for all methods was 59%, specificity 90% and accuracy of 82%. Notably, all four false‐positive cases except for one were from patients with primary sclerosing cholangitis or primary biliary sclerosis. There was no significant difference in sensitivity or specificity between biopsies procured by the two methods. The combined biopsy sensitivity for all modalities was 44% with a specificity of 100%. There was 70% concordance between cytology and biopsy cases. The overall specificity and sensitivity of the combined cytology and biopsy result was 85% and 65.3%, respectively. Ranking of factors that predict clinical diagnosis shows cytology results to surpass other parameters including pancreatic mass, age and stenosis length. Similarly, the presence of two cell populations and three‐dimensional clusters was not nearly as predictive of malignancy as single malignant cells. Conclusion: Biliary brush cytology specimens performed better than biopsies irrespective of whether they are procured during ERCP or cholangioscopy. The combination of cytology and biopsy had the best accuracy than either one alone.